Penerapan Pembelajaran Berbasis Praktikum untuk Meningkatkan Keterampilan Proses Sains Siswa SMP - Siti Khodijah Afsas; Sutikno Sutikno; Fianti Fianti (Departement of Mathematics Education, 2023)
The 2013 curriculum for science education trains students to learn independently and creatively. The teaching and learning process in it uses laboratory-based learning, where students are given the opportunity to experience and do things themselves. Throughout the process, they observe an object, analyze it, prove it, and draw their own conclusions about an object, situation, or process. These activities can enhance students' understanding. Process skills in science are skills that can help students solve various problems, and by applying laboratory activities, they can develop these process skills. The classification of science process skills is divided into two categories: basic process skills include observation, classification, measurement, and inference. Meanwhile, integrated science process skills include formulating hypotheses, identifying and controlling variables, conducting experiments, and interpreting data. Through science process skills, the concepts acquired by students will be more meaningful because their thinking skills will be further developed. Information technology and computers have developed so rapidly and have an incredible impact. Through virtual laboratories, the learning process becomes more interesting and interactive, teaching time can be reduced, the quality of learning can be improved, and the teaching and learning process can be done anytime and anywhere.